Analisis Mineral Liat Tanah Sawah Menggunakan X-Ray Diffractin (XRD) pada Tiga Kabupaten Berbeda di Yogyakarta - Mufriah, Dini (JURNAL AGROPLASMA, 2022)
The aim of this study is to analyze the types of clay minerals using x-ray diffraction (XRD) in several different locations in Yogyakarta, especially in paddy fields that have different types of soil management. The results of clay mineral analysis using XRD showed that the tillage layer on the paddy field in the Minggir sub-district, Sleman contains clay minerals of type 1:1, namely the type of Metahaloisite (Al2Si2O5(OH)4). While the results of the analysis of clay minerals in the top layer of paddy soil in Nanggulan sub-district, Kulonprogo and Pundong sub-district, Bantul showed a clay mineral of type 2:1 type Montmorillonite, where the Montmorillonite clay mineral contained in paddy soil in Nanggulan sub-district, Kulonprogo, had mineral crystallization higher better than the Montmorillonite clay mineral in the Pundong sub-district, Bantul.Keywords ï¼šx-ray diffraction (XRD),clay minerals, paddy fieldsÂ